THE EFFECT OF USING “BBC” YOUTUBE ON STUDENTS’ LISTENING ABILITY AT SMA PAHLAWAN JEMBER IN 2023 / 2024 ACADEMIC YEAR - Halida Listiani ,; Widaya Oktarini ,; Yeni Mardiyana , (Jurnal Cakrawala Ilmiah, 2024)
This research specifically examines the impact of "BBC" YouTube videos on students' listening abilities. The data analysis technique involved grouping the data and presenting it in tabular form to facilitate observation and evaluation. Calculations were then performed to answer the problem formulation and test the hypotheses. The research utilized a nonequivalent control group design to compare the experimental group's performance before and after the treatment. This research confirms that using BBC Learning English videos significantly improves students' listening skills at SMA Pahlawan Jember. This finding aligns with previous studies that highlight the effectiveness of integrating multimedia tools into language learning